An analysis of Indirectness of the Lexical Choice as Strategies of Communication among Prostitutes and Clients in Surabaya - Suswanto Ismadi Megah S (English Department, University of Riau Kepulauan, Batam,Indonesia, 2017)
This research was aimed to analyze indirectness of the lexical choices used in making offers of sale of ‘sex’ among prostitutes in Surabaya. The data obtained from of transcribed oral interactions among the ‘sellers’ and the clients. the subjects can be categorized as lower class prostitutes who offer their service for the price ranging from Rp.50,000,00 to 70.000,00 for one session The rates of the sex services are based on four criteria: length of service, age and physical features (for example skin colour and body shape) of the prostitutes as well as the skills they possess. The subjects also revealed that when the clients haggled for a price lower than the pasarane (standard price) price offered, it is a sign that the clients are of the lower socio-economic status. Observations of the subjects in action revealed that the subjects do indeed confirm or adjust the judgements made during the initial assessments of the clients’ social status as they begin to speak to the potential clients.Although Indonesian language is preferred, when Javanese language was used, lexical choices were made based on the different speech levels. The data found euphemism was mostly used communication among the ‘sellers’ and the clients